Effectiveness of Theoretical Learning Methods, Laboratory Practicum and Competency Certification in Operational Culinary Courses - Toni Ari Wibowo; Dian Fitriyana (Jurnal Edusci, 2026)
Background. Vocational colleges are universities that prepare human resources who are ready to work in industries supported by a curriculum that integrates with the industrial world. The learning process of theory, practical learning in the laboratory is an integration in the curriculum that can form a student competence, especially the operational course of culinary preparation. Purpose. The final results of theoretical learning activities and laboratory practicum for students will be measured in the form of competency certification so that the effectiveness of theoretical learning and laboratory practicum will be examined whether there is an influence and relationship to become a competent student with the measurement tool is the success of competency certification Method. The research used mixed methods, namely quantitative research using SPSS version 25 to determine the influence and relationship between variables, while qualitative research used NVivo to find out the picture of students through interviews on the effectiveness of learning theory and laboratory practicum on the success in competency certification for culinary operational courses. Conclusion. The effectiveness of learning theory and laboratory practicum in the culinary operations course will produce competence for each student, so that the success of competency certification is a form of competency for culinary operational courses.